Has there been a change in household saving behavior in the low inflation and interest rate environment? - Sami Oinonena; Matti E. E. Virén (Bank of Finland, 2022)
This paper examines whether the determinants of household saving have changed over time and whether they are the same across countries. Using a cross-country data for 34 OECD countries for the 1970-2019, we find that traditional saving rate specifications still perform strik ingly well and can explain the recent changes in household saving rates. As for the cross country differences in equilibrium saving rates, we have less success even though the basic estimating equation seems to fit reasonably well to individual country samples. We found that household saving is still very sensitive to changes in inflation and real income growth. Thus, decline in the household saving rate in the 1990s can mainly be attributed to these variables. Obviously, a decline of real interest rate has also pushed down the saving rate. Households seem to have reacted to changes in public sector as well as corporate sector saving so that there has been nontrivial degree of saving substitutability.
urn:nbn:fi:bof-202205101196
Keywords: E21; G51; 330; household saving; private saving; inflation; debt neutrality